2023
DOI: 10.3389/fped.2023.1160929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy analysis of paxlovid in children with hematological diseases infected with the omicron SARS-CoV-2 new variant

Abstract: ObjectiveTo summarize the clinical characteristics of children with hematological malignancies co-infected with novel coronavirus and explore the safety and effectiveness of Paxlovid treatment.MethodsFrom December 10, 2022, to January 20, 2023, the clinical data of children with hematological diseases diagnosed with novel coronavirus infection in the outpatient and emergency department of the Seventh Affiliated Hospital of Sun Yat-sen University were retrospectively analyzed.ResultsAccording to whether to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The emergency authorization also included "qualified" pediatric patients aged 12 to 18. In cohorts in which the efficacy of Paxlovid TM was evaluated in pediatric patients and in patients with oncologic conditions, the viral clearance time was significantly lower in those treated with Paxlovid TM (p = 0.033), but the levels of markers of inflammation were significantly greater (p < 0.05) [34]. On the other hand, Yan reported in his cohort that he found no significant differences in adverse effects, disease severity, or viral clearance times [35].…”
Section: Paxlovid Tm (Nirmatrelvir + Ritonavir)mentioning
confidence: 99%
“…The emergency authorization also included "qualified" pediatric patients aged 12 to 18. In cohorts in which the efficacy of Paxlovid TM was evaluated in pediatric patients and in patients with oncologic conditions, the viral clearance time was significantly lower in those treated with Paxlovid TM (p = 0.033), but the levels of markers of inflammation were significantly greater (p < 0.05) [34]. On the other hand, Yan reported in his cohort that he found no significant differences in adverse effects, disease severity, or viral clearance times [35].…”
Section: Paxlovid Tm (Nirmatrelvir + Ritonavir)mentioning
confidence: 99%
“…Another study conducted by Li et al explored the clinical efficacy of Paxlovid in children with a baseline hematological malignancy who were diagnosed with a SARS-CoV-2 infection. Among the Paxlovid and non-Paxlovid cohorts, it was indicated that children who received the oral antiviral treatment demonstrated shorter times of viral clearance and no adverse reactions to treatment, but on the other hand, underwent more extended periods of fever and presented with higher inflammation markers [101].…”
Section: Childrenmentioning
confidence: 99%